PENGEMBANGAN LANDING PAGE EDUKATIF BERBASIS PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) SUARA DEMOKRASI DI SMP BINA SEJAHTERA SUKMAJAYA DEPOK - Romdoni, Aceng; Abduh, Mohamad; Rumiati, Sri (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
This study aims to develop an Educational Landing Page media based on the Pancasila Student Profile Strengthening Project (P5) with the theme Voice of Democracy as a learning tool that can improve the leadership and justice character of junior high school students. This study uses the Research and Development (R&D) method with the Borg and Gall development model. The research subjects were eighth grade students of Bina Sejahtera Junior High School involving two classes, namely the experimental class and the control class. Data collection instruments included expert validation questionnaires, observations, reflective notes, and character tests before and after media use (pretest-posttest). The feasibility test was carried out by material, media, and communication experts, which showed that this media fell into the category of "Feasible" to "Very Feasible", especially in the interactivity aspect. The results of the effectiveness test using the independent sample t-test showed a significant difference between the experimental and control classes in improving leadership character (p = 0.006) and justice character (p = 0.008). The N-Gain value of 62.2% for leadership character and 84.5% for justice character indicates the effectiveness of the media in the medium to high category. Thus, this educational landing page media has proven to be feasible and effective as a contextual digital learning innovation that is able to support strengthening students' character in the context of the P5 Project. ABSTRAKPenelitian ini bertujuan untuk mengembangkan media Landing Page Edukatif Berbasis Proyek Penguatan Profil Pelajar Pancasila (P5) dengan tema Suara Demokrasi sebagai sarana pembelajaran yang mampu meningkatkan karakter kepemimpinan dan keadilan siswa SMP. Penelitian ini menggunakan metode Research and Development (R&D) dengan model pengembangan Borg dan Gall. Subjek penelitian adalah siswa kelas VIII SMP Bina Sejahtera dengan melibatkan dua kelas, yaitu kelas eksperimen dan kelas kontrol. Instrumen pengumpulan data meliputi angket validasi ahli, observasi, catatan reflektif, serta tes karakter sebelum dan sesudah penggunaan media (pretest-posttest). Uji kelayakan dilakukan oleh ahli materi, media, dan komunikasi, yang menunjukkan bahwa media ini masuk dalam kategori “Layak” hingga “Sangat Layak”, terutama pada aspek interaktivitas. Hasil uji efektivitas menggunakan independent sample t-test menunjukkan terdapat perbedaan yang signifikan antara kelas eksperimen dan kontrol terhadap peningkatan karakter kepemimpinan (p = 0,006) dan karakter keadilan (p = 0,008). Nilai N-Gain sebesar 62,2% untuk karakter kepemimpinan dan 84,5% untuk karakter keadilan menunjukkan efektivitas media dalam kategori sedang hingga tinggi. Dengan demikian, media landing page edukatif ini terbukti layak dan efektif sebagai inovasi pembelajaran digital kontekstual yang mampu mendukung penguatan karakter siswa dalam konteks Projek P5